Theory and application for the system of fractional Burger equations with Mittag leffler kernel - Korpinar, Zeliha; İnç, Mustafa; Bayram, Mustafa (Elsevier Science Inc, 2020)
In this work, the system of fractional Burger differential equations are presented as a new fractional model for Atangana-Baleanu fractional derivative with Mittag leffler kernel. The approximate consequences are analysed by applying an recurrent process. The existence and uniquenes of solution for this system is discussed. In order to appear the effects of several parameter and variables on the movement, the approximate results are showed in graphics and are compared with obtained solutions for two different derivative in tables. (C) 2019 Elsevier Inc. All rights reserved.
Keywords: System of fractional Burger equations; Atangana-Baleanu derivative; Mittag-leffler kernel; Existence and uniquenes; Series solution